Fear of failure in conservation: The problem and potential solutions to aid conservation of extremely small populations. (April 2015) - Meek, Mariah H.; Wells, Caitlin; Tomalty, Katharine M.; Ashander, Jaime; Cole, Esther M.; Gille, Daphne A.; Putman, Breanna J.; Rose, Jonathan P.; Savoca, Matthew S.; Yamane, Lauren; Hull, Joshua M.; Rogers, Deborah L.; et al.
Highlights: In conservation, procrastination can be driven by a fear of failure. The fear of failure can be driven by uncertainty or upsetting important others. We present solutions to address these roadblocks. Increased cooperation and new methods for evaluating success will provide solutions. Increased information-sharing and advanced decision making tools will also help. Abstract: The potential for extirpation of extremely small populations (ESPs) is high due to their vulnerability to demographic and environmental stochasticity and negative impacts of human activity. We argue that conservation actions that could aid ESPs are sometimes delayed because of a fear of failure. In human psychology, the fear of failure is composed of several distinct cognitive elements, including "uncertainty about the future" and "upsetting important others." Uncertainty about the future is often driven by information obstacles in conservation: information is either not easily shared among practitioners or information is lacking. Whereas, fear of upsetting important others can be due to apprehension about angering constituents, peers, funders, and other stakeholders. We present several ways to address these fears in hopes of improving the conservation process. We describe methods for increased information sharing and improved decision-making in the face of uncertainty, and recommend a shift in focus to cooperative actions and improving methods for evaluating success. Our hope is that by tackling stumbling blocks due to the apprehension of failure, conservation and management organizations can take steps to move from fear to action.